(untitled) (Brazilian Journal of Radiation Sciences, 2019)
The determination of silicon (Si), total uranium (U) and impurities in uranium-silicide (U3Si2) samples by wavelength dispersion X-ray fluorescence technique (WDXRF) has been already validated and is currently implemented at IPEN’s X-Ray Fluorescence Laboratory (IPEN-CNEN/SP) in São Paulo, Brazil. Sample preparation requires the use of approximately 3 g of H3BO3 as sample holder and 1.8 g of U3Si2. However, because boron is a neutron absorber, this procedure precludes U3Si2 sample’s recovery, which, in time, considering routinely analysis, may account for significant unusable uranium waste. An estimated average of 15 samples per month is expected to be analyzed by WDXRF, resulting in approx. 320 g of U3Si2 that wouldn’t return to the nuclear fuel cycle. This not only impacts in production losses, but generates another problem: radioactive waste management. The purpose of this paper is to present the mathematical models that may be applied for the correction of systematic errors when H3BO3 sample holder is substituted by cellulose-acetate [C6H7O2(OH)3-m(OOCCH3)m], m = 0 3, thus enabling U3Si2 sample’s recovery. The results demonstrate that the adopted mathematical model is statistically satisfactory, allowing the optimization of the procedure.U3Si2, XRF, WDXRF.